Using a Feedback Environment to Improve Creative Performance: A Dynamic Affect Perspective - Gong, Zhenxing; Zhang, Na (Frontiers in Psychology, 2017)
Prior research on feedback and creative performance has neglected the dynamic nature of affect and has focused only on the influence of positive affect. We argue that creative performance is the result of a dynamic process in which a person experiences a phase of negative affect and subsequently enters a state of high positive affect that is influenced by the feedback environment. Hierarchical regression was used to analyze a sample of 264 employees from 7 industry firms. The results indicate that employees’ perceptions of a supportive supervisor feedback environment indirectly influence their level of creative performance through positive affect (t2); the negative affect (t1) moderates the relationship between positive affect (t2) and creative performance (t2), rendering the relationship more positive if negative affect (t1) is high. The change in positive affect mediates the relationship between the supervisor feedback environment and creative performance; a decrease in negative affect moderates the relationship between increased positive affect and creative performance, rendering the relationship more positive if the decrease in negative affect is large. The implications for improving the creative performances of employees are further discussed.